THE ORIGIN, DIAGNOSIS AND MODERN CLINICAL DIAGNOSTIC METHODS OF MYOCARDIAL INFARCTION - Lenura Madjidovna, Appazova; Dil'shod Firdavsovna, Shaymatova; Oyjamol Narzullayevna, Uzoqova (PT. Antis International Publisher, 2025)
Objective: This study aims to explore the origin, diagnosis, and modern clinical diagnostic methods of myocardial infarction, a critical condition caused by the disruption of blood supply to the heart muscle. Method: A comprehensive review of current literature and clinical guidelines was conducted, focusing on the pathophysiological mechanisms, diagnostic criteria, and advancements in diagnostic technologies. The study analyzed data from clinical trials, imaging techniques, and biomarker evaluations to assess the effectiveness of contemporary diagnostic approaches. Results: The findings indicate that myocardial infarction predominantly results from coronary artery occlusion, leading to ischemia and necrosis of the myocardial tissue. Diagnostic advancements include high-sensitivity cardiac troponin assays, electrocardiography (ECG), echocardiography, and coronary angiography, which have significantly improved early detection and risk stratification. Additionally, non-invasive imaging modalities such as cardiac MRI and CT angiography enhance diagnostic accuracy. Novelty: This study highlights the integration of novel biomarkers with advanced imaging techniques as a transformative approach in the early diagnosis and management of myocardial infarction, offering new insights into improving patient outcomes through rapid and precise clinical assessment.